2015
DOI: 10.1038/srep13327
|View full text |Cite
|
Sign up to set email alerts
|

Reconsolidation of a cocaine associated memory requires DNA methyltransferase activity in the basolateral amygdala

Abstract: Drug addiction is considered an aberrant form of learning, and drug-associated memories evoked by the presence of associated stimuli (drug context or drug-related cues) contribute to recurrent craving and reinstatement. Epigenetic changes mediated by DNA methyltransferase (DNMT) have been implicated in the reconsolidation of fear memory. Here, we investigated the role of DNMT activity in the reconsolidation of cocaine-associated memories. Rats were trained over 10 days to intravenously self-administer cocaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
(111 reference statements)
1
24
0
Order By: Relevance
“…Additionally, we found that the reconsolidation of morphine withdrawal memory was impaired by injection of a DNMT inhibitor into the agranular insular cortex or basolateral amygdala . Similarly, intra–basolateral amygdala infusion of the DNMTs inhibitor 5‐azacytidine hindered the reconsolidation of cocaine associated memory and then decreased subsequent reinstatement induced by cues or drug priming . All these evidence suggests that DNA methylation in different brain regions are involved in different aspects and/or stages of drug addiction.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, we found that the reconsolidation of morphine withdrawal memory was impaired by injection of a DNMT inhibitor into the agranular insular cortex or basolateral amygdala . Similarly, intra–basolateral amygdala infusion of the DNMTs inhibitor 5‐azacytidine hindered the reconsolidation of cocaine associated memory and then decreased subsequent reinstatement induced by cues or drug priming . All these evidence suggests that DNA methylation in different brain regions are involved in different aspects and/or stages of drug addiction.…”
Section: Discussionmentioning
confidence: 64%
“…Previous reports have demonstrated that cocaine can modulate the levels of targeted genes by epigenetic mechanisms (promoter DNA methylation). 31,32 DNMTs including, DNMT1, 3a, and 3b, are the proteins responsible for regulating and maintaining promoter DNA methylation levels. 33 To investigate whether DNMTs are associated with cocaine-mediated miR-124 downregulation, we examined the protein levels of DNMT1 and 3a in those cocaine-treated BV-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work in rodents has been aimed at targeting the reconsolidation process and interfering with drug-associated memories to reduce craving and prolong abstinence (cf., Taylor et al, 2009;Sorg 2012;Torregrossa and Taylor, 2013;Everitt, 2014;Taylor and Torregrossa, 2015;Torregrossa and Taylor, 2016). Indeed, it has been demonstrated that specifically manipulating cocaine-cue memories following memory retrieval using pharmacological agents can block the reconsolidation of these memories and reduce drug-seeking behavior in rats (Lee et al, 2005(Lee et al, , 2006Sanchez et al, 2010;Wan et al, 2014;Shi et al, 2015;Merlo et al, 2015). However, most of these studies to date have used intracranial drug infusions.…”
Section: Systemic Garcinol As a Compound With Translational Utilitymentioning
confidence: 99%